THU0227 Early Rheumatoid Arthritis is Associated with Periarticular Demineralisation of the Metcarpal Bones. (10th June 2014) - Pfeil, A.; Langer, H.E.; Reinhardt, L.; Langer, A.; Werner, S.G.; Boettcher, J.; Oelzner, P.; Wolf, G.
Abstract : Background: Digital X-ray radiogrammetry (DXR) is an established computer-based technique for the quantification of periarticular hand bone mineral density at the metacarpal bones. Metacarpal bone mineral density function as a surrogate marker of radiological progression. Objectives: The aim of this study was to evaluate cortical hand bone mineral density at the metacarpal bones in patients with early rheumatoid arthritis (ERA) at the time point of diagnosis and follow up at 12 months. Methods: The study included 170 patients with ERA (duration of symptoms 9.9±7.8 months). The prognosis of ERA was stratified by the Visser Score. Based on the Visser Score four risk groups concerning the development of erosion were defined: low risk (<25%), moderate risk (25-50%), high risk (50-75%) and very high risk (>75%). Additional the therapeutic modalities were adapted at the risk groups (low risk: NSAR, moderate risk: corticosteroids, high risk: conventional DMARD, very risk: biologic DMARD). X-rays of the hand were acquired at baseline and after 12 months. Metacarpal Bone Mineral Density (DXR-BMD), Metacarpal Index (DXR-MCI), Cortical Index (DXR-CT) and Metacarpal Bone Width (DXR-W) was measured by DXR (Version 2, Sectra, Sweden). The T-Score as an age and gender independent parameter of DXR-BMD was calculated to compare DXR-BMD in ERA to DXR-BMD in healthy subjects. Results: At baseline in all 170 patients the T-Score (-0.591 SD) of DXR-BMD was significantly reduced. No change of DXR-BMD (-0.9%; p = not significant) from 0.548 g/cm 2 (baseline) to 0.543 g/cm 2 (month 12) was revealed. A minimal reduction from 0.176 cm (baseline) to 0.174 (month 12) was verified for DXR-CT (-1.1%; p = not significant). No change was observed for DXR-MCI. Conclusions: Patients with ERA present at the time point of diagnosis a reduced periarticular mineralisation of the metacarpal bones as quantified by the T-Score. With a risk stratified treatment in ERA no change of metacarpal bone mineral density was observed by DXR. The results highlights the usefulness of the DXR-parameters as radiological surrogate marker in ERA. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3678